2016
DOI: 10.1080/09585192.2016.1233447
|View full text |Cite
|
Sign up to set email alerts
|

Hard, soft or ambidextrous? Which influence style promotes managers’ task performance and the role of political skill

Abstract: Hard, soft or ambidextrous? Which influence style promotes managers' task performance and the role of political skillAmbidexterity at the manager level focuses on the crucial, but underexplored, role of managers' knowledge, skills, and behaviors to address competing demands and promote organizational ambidexterity. As such, to successfully complete their assigned duties, managers need to employ the appropriate interpersonal style and calibrate their behavior to different contextual demands. This study highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 130 publications
(162 reference statements)
1
25
0
Order By: Relevance
“…Burgess et al (2015) studied a macro-level (external regulatory pressures) and a micro-level (individual), and Kassotaki et al (2019) analyzed the way ambidexterity penetrates across three different levels (senior executives, middle managers, and employees) and the way ambidexterity penetrates through the whole organization. Moreover, although some papers seem to propose a multilevel theoretical model, only few studies use multilevel statistical techniques (Y. C. Chang et al, 2016;Jasmand et al, 2012;Kapoutsis et al, 2019;Kauppila & Tempelaar, 2016;Kobarg et al, 2017;Li et al, 2015;Mom et al, 2019;Schultz et al, 2013;Van der Borgh et al, 2017;Yu et al, 2018). Most of these studies analyze the individual level together with the organization or unit level.…”
Section: Issue 7: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Burgess et al (2015) studied a macro-level (external regulatory pressures) and a micro-level (individual), and Kassotaki et al (2019) analyzed the way ambidexterity penetrates across three different levels (senior executives, middle managers, and employees) and the way ambidexterity penetrates through the whole organization. Moreover, although some papers seem to propose a multilevel theoretical model, only few studies use multilevel statistical techniques (Y. C. Chang et al, 2016;Jasmand et al, 2012;Kapoutsis et al, 2019;Kauppila & Tempelaar, 2016;Kobarg et al, 2017;Li et al, 2015;Mom et al, 2019;Schultz et al, 2013;Van der Borgh et al, 2017;Yu et al, 2018). Most of these studies analyze the individual level together with the organization or unit level.…”
Section: Issue 7: Methodsmentioning
confidence: 99%
“…Third, new concepts related to individual ambidexterity have been identified in our systematic review. Kapoutsis et al (2019) introduce the concept of "influence tactic ambidexterity" at the manager level to denote the frequent use of both hard (maintaining efficiency and control through tactics such as exhibit higher task performance) and soft influence tactics (e.g., motivation, engagement, risk-taking, and trust). Kassotaki et al (2019) introduce the term "ambidexterity penetration" that refers to the enactment of ambidexterity across multiple organizational levels, distinguishing among horizontal, vertical, and organizational penetration.…”
Section: Issue 2: Concept and Tensions In Individual Ambidexteritymentioning
confidence: 99%
“…In view of this, they have adequate energy to carry out extra work tasks that increase organizational efficiency. Studies on the moderators of the POP–job attitude association have revealed that the adverse effects of POP can be lessened by employees' skills or attributes (Kapoutsis et al, 2016 ; Bentley et al, 2017 ). Our finding on the moderating role of WE extends previous scholarly works that proposed the need for promising organizational features, such as WE, as a driver to translate into positive job attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…As established in the literature, individuals who are endowed with PS play an instrumental role in getting along with employees, who must endure this advantage over them (Perrewé et al, 2004 ; Butt et al, 2017 ; García-chas et al, 2018 ). These individuals with PS easily adjust to any political environment and efficiently employ social skills in motivating subordinates or employees in an organization to boost their JS (Kapoutsis et al, 2016 ; Cong et al, 2017 ). In addition, PS helps employees to communicate barriers and thus minimizes the stress resulting from ambiguity (Crawford et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Exploring 1,449 internal and external network links of 79 senior managers in a management consulting firm, they showed that there are significant differences in the density, contact heterogeneity, and informality of ties in the networks of individual senior managers engaged in both exploration and exploitation vs. managers that are dealing with either exploratory or exploitative activities (Rogan and Mors, 2014). Moreover, Kapoutsis, Papalexandris, & Thanos (2016) focused on the role of the individual in the ambidexterity process by presenting the concept of 'influence tactic ambidexterity' to illustrate the frequent use of both soft and hard influences between individuals and its impact on task performance and concluded that political skill positively moderates the relationship between influence tactic ambidexterity and a manager's task performance.…”
Section: Connecting Work Intensification and Extremes With Organizatimentioning
confidence: 99%